Farmers in the transition toward sustainability: what is the role of their entrepreneurial identity? - Rossi, Eleonora Sofia; Materia, Valentina C.; Caracciolo, Francesco; Blasi, Emanuele; Pascucci, Stefano (Frontiers in Sustainable Food Systems, 2023)
Introduction The European Union has recently prompted a shift toward Ecological Intensification (EI) practices, aiming to harmonize agricultural productivity and environmental conservation. Despite the benefits of EI, its implementation has been limited, as farmers face challenges in business reorganization and supply chain adaptation. This paper investigates the role of contract farming (CF) in promoting the adoption of sustainable practices among Italian wheat producers. Specifically, it analyzes the influence of farmers’ entrepreneurial identity on their engagement in such initiatives. Methods Using the case study of Barilla Group’s Carta del Mulino initiative, an innovative contract farming scheme incentivizing sustainable EI practices, the study explores the relationship between entrepreneurial identity and participation in CF schemes supporting EI. Data from a sample of 314 soft wheat farmers in four regions of Northern Italy were collected to examine the role of entrepreneurial identity in the adoption of sustainable practices and participation in CF schemes. To evaluate the research hypotheses, two distinct econometric models were developed. Results and discussion The findings reveal that farmers with a more developed entrepreneurial identity are more likely to adopt more sustainable agricultural practices and engage in contractual schemes involving EI practices. The study highlights the importance of fostering and supporting farmers’ entrepreneurial identity while increasing their knowledge of alternative agricultural techniques to address the challenges of the agricultural sector. This integration of individual perspectives (entrepreneurial identity) with a systems view (contract farming schemes) offers valuable insights for future research, policy, and practice in agri-food systems sustainability.